2015
DOI: 10.1074/jbc.m115.671222
|View full text |Cite
|
Sign up to set email alerts
|

Nonantibiotic Effects of Fluoroquinolones in Mammalian Cells

Abstract: Background: Fe(II)-dependent dioxygenases regulate epigenetic control, collagen maturation, and HIF degradation.Results: Iron chelation by fluoroquinolone antibiotics results in DNA and histone hypermethylation, suppression of collagen prolyl hydroxylation, and inhibition of HIF mRNA translation.Conclusion: Dioxygenase inhibition may explain renal toxicity and tendinopathy side effects of fluoroquinolones.Significance: This study suggests mechanisms for obscure fluoroquinolone-associated side effects and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 75 publications
(88 reference statements)
0
61
0
2
Order By: Relevance
“…In relation to tendon biology, expression of G9a, a methyltransferase with specific affinity to the ninth lysine residue of histone three, was shown to regulate cellular differentiation in mouse tenocytes by expression of tenogenic transcription factors, including Scleraxis and Mohawk, which have been heavily studied as necessary modulators for proper tendon development . Additionally, the use of fluoroquinolones (linked to tendinopathy in human patients) in human embryonic kidney cell cultures resulted in the inhibition of DNA methylases, collagen prolyl 4‐hydroxylases, and hypoxia inducible factor 1a (also linked to tendinopathy), suggesting a mechanistic epigenetic link to chronic tendinopathy …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to tendon biology, expression of G9a, a methyltransferase with specific affinity to the ninth lysine residue of histone three, was shown to regulate cellular differentiation in mouse tenocytes by expression of tenogenic transcription factors, including Scleraxis and Mohawk, which have been heavily studied as necessary modulators for proper tendon development . Additionally, the use of fluoroquinolones (linked to tendinopathy in human patients) in human embryonic kidney cell cultures resulted in the inhibition of DNA methylases, collagen prolyl 4‐hydroxylases, and hypoxia inducible factor 1a (also linked to tendinopathy), suggesting a mechanistic epigenetic link to chronic tendinopathy …”
mentioning
confidence: 99%
“…19 Additionally, the use of fluoroquinolones (linked to tendinopathy in human patients 20 ) in human embryonic kidney cell cultures resulted in the inhibition of DNA methylases, collagen prolyl 4-hydroxylases, and hypoxia inducible factor 1a (also linked to tendinopathy 21 ), suggesting a mechanistic epigenetic link to chronic tendinopathy. 22 While these recent studies suggest the important role of epigenetics in tendon biology, to our knowledge there are no published studies on analyses for altered DNA methylation and histone modification in human tendinopathies or animal models of the disease. The current study was carried out, using a murine model of Achilles tendinopathy, to identify changes in expression of epigenetic modification enzymes, and to subsequently perform a genomewide screening for changes in methylation of gene promoter regions associated with the development of the disease.…”
mentioning
confidence: 99%
“…But the potential for mitochondrial damage still isn't widely appreciated 8 , reported that fluoroquinolones can bind to iron atoms from the active sites of several enzymes that modify DNA, leading to epigenetic changes that might be related to some of the drugs' side effects.…”
Section: Mitochondrial Damagementioning
confidence: 99%
“…Antibiotics can have a variety of microbiota-independent effects on mammalian cells. Antibiotics can illicit profound changes in host gene expression in both conventional and germ-free mice (11), alter mammalian metabolic pathways and impair the phagocytic activity of immune cells (12), induce mitochondrial dysfunction (13, 14), and inhibit histone demethylases (15). Additionally, Gopinath et al recently demonstrated that aminoglycoside antibiotics can confer microbiota-independent antiviral resistance against both DNA and RNA viruses by upregulating expression of interferon-stimulated genes (16).…”
Section: Introductionmentioning
confidence: 99%